Impact of administration route on nanocarrier biodistribution in a murine colitis model - Catherine C. Applegate; Hongping Deng; Brittany L. Kleszynski; Tzu-Wen L. Cross; Christian J. Konopka; L. Wawrzyniec Dobrucki; Erik R. Nelson; Matthew A. Wallig; Andrew M. Smith; Kelly S. Swanson (Journal of Experimental Nanoscience, 2022)
The incidence of inflammatory bowel disease (IBD) is increasing worldwide. Although current diagnostic and disease monitoring tests for IBD sensitively detect gut inflammation, they lack the molecular and cellular specificity of positron emission tomography (PET). In this proof-of-concept study, we use a radiolabeled macrophage-targeted nanocarrier probe (64Cu-NOTA-D500) administered by oral, enema, and intraperitoneal routes to evaluate the delivery route dependence of biodistribution across healthy and diseased tissues in a murine model of dextran sodium sulfate (DSS)-induced colitis. High inter-subject variability of probe uptake in intestinal tissue was reduced by normalization to uptake in liver or total intestines. Differences in normalized uptake between healthy and DSS colitis animal intestines were highest for oral and IP routes. Differences in absolute liver uptake reflected a possible secondary diagnostic metric of IBD pathology. These results should inform the preclinical development of inflammation-targeted contrast agents for IBD and related gut disorders to improve diagnostic accuracy.